The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1079063220981889
|View full text |Cite
|
Sign up to set email alerts
|

The Victim–Offender Overlap in Sexual Offending: Exploring a Community-Based Sample of Young Adults in Hong Kong

Abstract: This study examines the overlap between sexual offending perpetration and victimization among 1,171 participants (18–40 years) in Hong Kong. Testing the theoretical propositions of several criminological theories (i.e., self-control, general strain, routine activity, and social learning), the participants’ prevalence of general, penetrative, and nonpenetrative sexual offending perpetration and victimization are explored. The findings indicated that sexual offending perpetration and victimization are generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…For instance, having an interest in paraphilic behavior that is illegal in nature (e.g., biastophilia [rape] or pedophilia [sex with underage children]) may pose a serious threat to the public. Besides, problematic sexual interests and behavior are associated with a number of harmful consequences, including heightened risk of sexually transmitted infections (Yoon, Houang, Hirschfield, & Downing, 2016), interpersonal problems (Winder, Fedoroff, Grubin, Klapilová, Kamenskov, Tucker, et al, 2019), physical injuries (Carnes, 1991), and sexual (re)offending behavior (Chan, 2020a;Hanson & Morton-Bourgon, 2005). In view of the potential high risk of adverse public health outcomes, it is worthwhile to understand this phenomenon in Hong Kong, especially the factors associated with paraphilic interests, to effectively identify and intervene in a timely manner on behalf of those who are at greatest risk for such outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, having an interest in paraphilic behavior that is illegal in nature (e.g., biastophilia [rape] or pedophilia [sex with underage children]) may pose a serious threat to the public. Besides, problematic sexual interests and behavior are associated with a number of harmful consequences, including heightened risk of sexually transmitted infections (Yoon, Houang, Hirschfield, & Downing, 2016), interpersonal problems (Winder, Fedoroff, Grubin, Klapilová, Kamenskov, Tucker, et al, 2019), physical injuries (Carnes, 1991), and sexual (re)offending behavior (Chan, 2020a;Hanson & Morton-Bourgon, 2005). In view of the potential high risk of adverse public health outcomes, it is worthwhile to understand this phenomenon in Hong Kong, especially the factors associated with paraphilic interests, to effectively identify and intervene in a timely manner on behalf of those who are at greatest risk for such outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that individuals who had paraphilic interests or had been diagnosed with paraphilias were more likely to engage in hypersexual activities, such as having multiple sexual partners, a high sexual appetite and preoccupation, and high rates of sexual behavior (Kafka and Hennen, 2003;Långström and Hanson, 2006;Kafka, 2009;Chan, 2021). Indeed, Chan (2020a) found that high levels of RSB and paraphilic interests were significantly associated with sexual offending behavior. Relative to previous studies, participants in this study reported comparatively lower level of paraphilic interests.…”
Section: Discussionmentioning
confidence: 91%
“…In some cases, however, these behaviors persist from childhood into adulthood, with pathological risk factors and poor life outcomes (Moffit, 2018). Although the relationship between childhood victimization and subsequent problematic outcomes is well established, the available knowledge is mainly related to juvenile or adult offenders (DeLisi et al, 2014; Ford et al, 2013; Marini et al, 2014; Miley et al, 2020; Wanamaker et al, 2022) that have already been identified as offenders, or community samples of adults or young adults (Boateng & Campbell, 2022; H. C. Chan, 2021; Chopin et al, 2022; Jespersen et al, 2009).…”
Section: Objectivesmentioning
confidence: 99%